Transcriptomic analysis of rice cultivars with distinct resistance mechanisms to Xanthomonas oryzae pv. oryzicola reveals novel components and candidate genes associated with bacterial leaf streak - Win, Moe Moe Kyi; Aesomnuk, Wanchana; Dumhai, Reajina; Ruengphayak, Siriphat; Gray, Julie E.; Bar, Ido; Ruanjaichon, Vinitchan; Wanchana, Samart; Arikit, Siwaret (Frontiers in Plant Science, 2025)
Xanthomonas oryzae pv. oryzicola causes bacterial leaf streak, a rice disease that can lead to substantial yield losses. Although an xa5-based signaling pathway is known to confer resistance to this disease, alternative stable and broad-spectrum resistance mechanisms will be critical for sustainable management. In this regard, we characterized NDCMP49, a Thai rice variety with strong resistance to bacterial leaf streak but lacking xa5-based resistance. Transcriptomes of NDCMP49 were compared with DV85, a rice variety with xa5-based resistance, and HCS, a bacterial leaf streak susceptible variety, at 0- and 9-hours post-inoculation with X. oryzae pv. oryzicola. Analysis of differentially expressed genes revealed a less transcriptional response in the two resistant varieties than in the susceptible variety. Nonetheless, during the first nine hours of infection, all varieties showed differential expression of receptor-like kinases, NB-LRR proteins, WRKY and NAC transcription factors, heat shock proteins, and chitinases, indicating the involvement of pathogen pattern-triggered immunity and effector-triggered immunity pathways. Interestingly, genes previously associated with the Xa21-mediated resistance to closely related pathogen Xanthomonas oryzae pv. oryzae were also identified. The genotype-phenotype association analysis performed on 249 rice accessions showed that RIR1b has some InDels in the gene’s coding region, which separates the accessions according to response to X. oryzae pv. oryzicola. Moreover, 2 bp insertions in the regulatory region led to up-regulation of RIR1b in NDCMP49 over DV85 and HCS. The genes identified here are valuable candidates for functional characterization. Targeting these genes would advance breeding rice varieties with strong resistance to bacterial leaf streak and other major diseases.